واقع التجارة الإلكترونية والتحديات التي تواجهها عربياً ومحلياً - أبازيد, ثناء (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى تسليط الضوء على مفهوم التجارة الإلكترونية وأهميتها وآثارها الاقتصادية، ثم استعراض لواقعها عالمياً والتركيز على الصورة الحالية لها في الدول العربية وسوريا، وأخيراً يستعرض هذا البحث لأهم التحديات والعقبات التي تقف أمام تطور التجارة الإلكترونية في الوطن العربي وسوريا، وصولاً لبعض الاقتراحات التي نراها مناسبة لدفع هذا النوع من التجارة نحو الأمام. This research aims to highlight the concept of Electronic Commerce , (EC), its importance and its economic effects. This will be followed by describing this concept within the global arena. The Arab and Syrian contexts, In particular are going to be the focus of this research. Finally, the study explains the most importance influences other impediments that face the development of EC in the Arab world and Syria. This research will suggest some suitable means that might garanttee an advanced pace of EC in this specific area..